PRE-SERVICE ENGLISH TEACHERS' TRANSLANGUAGING PRACTICES - Riyanti, Dwi (STKIP Persada Khatulistiwa Sintang, 2024)
Translanguaging in which more than one language is allowed to be used in the classroom is currently a trending issue that has been widely claimed to be helping students to foster foreign language learning, including learning English as a foreign language. While research on translanguaging within the EFL settings has been abundant, only a few studies are within the Indonesian context. Thus, it is crucial to investigate how translanguaging is employed within a high school context in Indonesia.Â Employing a qualitative case study, the study involved four pre-service English teachers who had a teaching practicum at a senior high school. The data were gathered from observing the recorded videos of participantsâ€™ teaching practicum teaching practicum as the participants while having a teaching practicum, interviewing them as a follow up of the observation, and open-ended questionnaire. The obtained data were analyzed thematically based on emerging themes. The findings indicate that pre-service teachers translanguage as they teach their students for various reasons, suggesting that translanguaging is important to enhance students' comprehension and to create a less stressful classroom atmosphere.